Protection from cyanide‐induced brain injury by the Nrf2 transcriptional activator carnosic acid. (11th March 2015) - Zhang, Dongxian; Lee, Brian; Nutter, Anthony; Song, Paul; Dolatabadi, Nima; Parker, James; Sanz‐Blasco, Sara; Newmeyer, Traci; Ambasudhan, Rajesh; McKercher, Scott R.; Masliah, Eliezer; Lipton, Stuart A.
Abstract Cyanide is a life‐threatening, bioterrorist agent, preventing cellular respiration by inhibiting cytochrome c oxidase, resulting in cardiopulmonary failure, hypoxic brain injury, and death within minutes. However, even after treatment with various antidotes to protect cytochrome oxidase, cyanide intoxication in humans can induce a delayed‐onset neurological syndrome that includes symptoms of Parkinsonism. Additional mechanisms are thought to underlie cyanide‐induced neuronal damage, including generation of reactive oxygen species. This may account for the fact that antioxidants prevent some aspects of cyanide‐induced neuronal damage. Here, as a potential preemptive countermeasure against a bioterrorist attack with cyanide, we tested the CNS protective effect of carnosic acid (CA), a pro‐electrophilic compound found in the herb rosemary. CA crosses the blood–brain barrier to up‐regulate endogenous antioxidant enzymes via activation of the Nrf2 transcriptional pathway. We demonstrate that CA exerts neuroprotective effects on cyanide‐induced brain damage in cultured rodent and human‐induced pluripotent stem cell‐derived neurons in vitro, and in vivo in various brain areas of a non‐Swiss albino mouse model of cyanide poisoning that simulates damage observed in the human brain. Cyanide, a potential bioterrorist agent, can produce a chronic delayed‐onset neurological syndrome that includes symptoms of Parkinsonism. Here, cyanide poisoning treated with the proelectrophillic compound carnosic acid, results in reduced neuronal cell death in both in vitro and in vivo models through activation of the Nrf2/ARE transcriptional pathway. Carnosic acid is therefore a potential treatment for the toxic central nervous system (CNS) effects of cyanide poisoning. ARE, antioxidant responsive element; Nrf2 (NFE2L2, Nuclear factor (erythroid‐derived 2)‐like 2).